A reassessment of the geochemical, phylogeny, morphology, and taxonomy of two crocodilian jaw remains of Paleogene from central Europe (Germany and Austria) - Karl , Hans-Volker; Tichy , Gottfried; safi, Amtyaz (International Journal of Biological Research, 2023)
Crocodiles are a conservative group of reptiles regarding their morphology and behaviour. Available Fossils are hence important to be studied for phylogeny, taxonomy and morphology. A fossil fragmentary crocodilian skull was found in lignite clay in the Paleogene sedimentary area from the Middle Oligocene Epoch of Sieglitz near Camburg at Saale river in Central Germany. This 20th century discovery documents a new species of Diplocynodon (Diplocynodon Haeckeli, described by Seidlitz in 1917). Another crocodile fossil was unearthed in 1878 from the Eocene Epoch, of Haunsberg near Sankt Pankraz in the province of Salzburg in Austria, which had been missing since 1970 and was recently rediscovered and identified. This rediscovered specimen, representing a crocodile mandible and an isolated tooth, which could belong to Asiatosuchus and not Diplocynodon. However, the morphology of isolated tooth is not a reliable source to identify it up to the generic level, so open taxonomy is used here for identification, it may be associated to the same or a new species. The new discoveries of fossils provide new characters enhancing our knowledge on a particular taxon and on the whole group.